2008
DOI: 10.1002/jmor.10614
|View full text |Cite
|
Sign up to set email alerts
|

Morphological relationships and leukocyte influence on steroid production in the epigonal organ‐ovary complex of the skate, Leucoraja erinacea

Abstract: In elasmobranchs, a unique association exists between an immune tissue, the epigonal organ (EO), and the gonads. In this study, the histological and vascular relationships of the EO and ovarian follicles of the little skate, Leucoraja erinacea, were assessed. Perfusions of Evans blue dye and Batson's monomer showed a shared vascular pathway from the gonadal artery into the epigonal-ovary complex, with blood first entering the EO and then perfusing the ovarian follicles. Histological studies demonstrated direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(58 reference statements)
2
7
0
Order By: Relevance
“…The erythrocytes described in the present study were similar to those reported for birds, reptiles, amphibians, teleost fish species and elasmobranchs (Lutton and Callard, 2008;Claver and Quaglia, 2009).…”
Section: Disscussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The erythrocytes described in the present study were similar to those reported for birds, reptiles, amphibians, teleost fish species and elasmobranchs (Lutton and Callard, 2008;Claver and Quaglia, 2009).…”
Section: Disscussionsupporting
confidence: 87%
“…These cells included eozinophil granulocytes, lymphocytes, thrombocytes and erythrocytes. The morphological structure and overall appearance of these cells in the epigonal organ of R. rhinobatos were similar to that observed in some other elasmobranchs , Wobbegong sharks, Orectolobus species (Old and Huveneers, 2006), skate Leucoraja erinacea (Lutton and Callard, 2008). In these species including R. rhinobatos the epigonal organ was directly associated with the gonads.…”
Section: Disscussionsupporting
confidence: 81%
“…Interestingly, these cells increase in number upon an infection [70]. Similarly, in the elasmobranch fish Little skate (Leucoraja erinacea) ovary, direct contact between leucocytes and the follicle wall as well as between the steroidogenic theca and granulosa cells has been demonstrated [71]. In the teleost fish gilthead seabream, acidophilic granulocytes appear in great numbers in the developing ovarian area during larval development, remaining until the area is totally developed [72], while in the adult gonad, they are restricted to the connective tissue that limits the testicular and ovarian areas and to the testicular interstitium [49].…”
Section: The Ovary Environment That Allows Immune Privilegementioning
confidence: 96%
“…Sharks and skates have been used in a number of laboratories for examination of immune system development and evolution. For instance, the function of the epigonal organ, an immune tissue intimately associated with the gonad and not present in mammals, has been studied in L. erinacea in experiments using in vitro techniques (Lutton & Callard, 2007, 2008 a,b ). Epigonal leucocytes in culture were influenced to undergo apoptosis upon exposure to progesterone, testosterone or dexamethasone (Lutton & Callard, 2007).…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%
“…Incubation of epigonal cells in co‐culture with cells isolated from the follicle wall of the ovary led to inhibition of production of oestrogen and testosterone. Conditioned medium from cultures of epigonal leucocytes caused, however, an increase in production of these steroids from follicle wall cells (Lutton & Callard, 2008 a ). Medium for these experiments was a 1:1 mixture of Dulbecco modified Eagle's medium and Ham's F12 medium at 1000 mOsmol, containing 100 mM sodium chloride, 350 mM urea and 72 mM trimethylamine oxide.…”
Section: Application Of Primary Culture Technologymentioning
confidence: 99%